Influence of Chrysoporthe deuterocubensis canker disease on the chemical properties and durability of Eucalyptus urograndis against wood rotting fungi and termite infestation - Dahali, Rasdianah; Lee, Seng Hua; Md Tahir, Paridah; Salim, Sabiha; Hishamuddin, Muhammad Syahmi; Che Ismail, Atikah; Khoo, Pui San; Krystofiak, Tomasz; Antov, Petar (Multidisciplinary Digital Publishing Institute, 2023)
In this study, the effects of stem canker disease caused by Chrysoporthe deuterocubensis on the chemical properties and durability of a Eucalyptus hybrid (E. urophylla x E. grandis) were investigated. Eleven-year-old healthy and infected trees were collected. The samples were grouped into four different classes based on the infection severity: healthy (class 1), moderately infected (class 2), severely infected (class 3), and very severely infected (class 4). The changes in chemical properties were evaluated via chemical analysis and Fourier transform infrared spectroscopy (FTIR) analysis. A resistance test against fungal decay (Pcynoporus sanguineus and Caniophora puteana) and termite (Coptotermes curvignathus) was also performed. The results showed that reductions in cellulose and hemicellulose content from 53.2% to 45.4% and 14.1% to 13.9%, respectively, were observed in the infected samples. Meanwhile, the percentages of lignin and extractives increased from 18.1% to 20.5% and 14.6% to 20.2%, respectively. The resistance against fungi and termites varied between severity classes. Generally, infected wood behaved better than healthy wood in terms of durability against fungi and termites. The durability classes for both tests were significantly improved, from resistant to highly resistant and poor to moderately resistant, respectively. These results suggest that E. urograndis that is infected by C. deuterocubensis might have a better potential use in lumber production with regard to its durability and processing cost compared to pulp and paper products.